Water Microgrids: The Future of Water Infrastructure Resilience. (2015) - Falco, Gregory J.; Webb, Wm. Randolf
Abstract: Microgrids have recently come into vogue as a potential solution to address the increasing number of power outages caused by extreme weather events that impact our cities and communities. Such events – often precipitated by increasing global temperatures and climate change – have repercussions that expand beyond damages to a city's electric infrastructure. Water infrastructure is similarly vulnerable to extreme weather events, resulting in significant impacts to clean water distribution, wastewater treatment, and stormwater management. Given this similarity, and other value drivers to be outlined, this paper proposes leveraging concepts behind electricity microgrids to develop a unified framework for microgrid application to promote water resilience in the face of our changing climate. Many parallels can be drawn between the electric grid and water infrastructure considering both are utilities that generate, store, and distribute an essential product that has been identified as a basic human right. Also similar to the electric grid, water infrastructure is aged and costly to redevelop. For both industries, microgrids are a potential solution that addresses aged infrastructure concerns while also being potentially more cost effective. In addition, by leveraging legacy infrastructural components while developing a new system within the system, microgrids provide redundancy, fortify vulnerabilities and secure the resource supply chain. This paper will investigate parallel components of electric and water infrastructure to provide a vision for future resilient water microgrids.